Understanding Attitudes Toward Police Surveillance: The Role of Authoritarianism, Fear of Crime, and Private-Sector Surveillance Attitudes - Conrey, Camille; Haney, Craig (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
Public attitudes toward domestic police surveillance have important implications for its political salience and regulation. An increasing number of jurisdictions have sought to regulate law enforcement surveillance, in part due to growing concerns over issues related to privacy, civil liberties, and the potential for bias (Beyea and Kebde 2021; Chivukula and Takemoto 2021; Smyth 2021). This study explores what factors help to predict and shape public attitudes toward police surveillance. Two groups of participants (n = 131 and n = 299) completed measures of authoritarianism, fear of crime, consumer surveillance technology use, and attitudes toward private-sector surveillance (such as surveillance by private companies, employers, or citizens) and police surveillance. Demographic factors (age, race/ethnicity, education level, gender, and political leaning) were also examined. Of these factors, legal authoritarianism, level of interaction with surveillance-related consumer technology, and attitudes toward private-sector surveillance were positively associated with the acceptance of police surveillance.